O intelectual modernista como artista: Rubén Dario - Zanetti, Susana Emilce (2007)
This article reviews the intellectual career of Rubén Darío, profiling the artist's position in modernism (1880-1910), the first concrete movement among Hispano-American writers, which substantially renewed the literary output in Spanish. Incorporated into the modern market as a journalist and immigrant, the article follows Darío's intellectual life from the archaic cultural context of his native Nicaragua to some of the foremost Hispano-American (Buenos Aires) and European (Madrid, Paris) centres, and considers his demands for aesthetic autonomy and his constant affirmation of the poet's authority to intervene in discussions relating to modern society and culture. Here we see the emergence of his commitment to the creation of a Latin America founded on new ties of solidarity and union with Spain, in the face of the threatening advance of the United States.